Arbuscular mycorrhizal fungi (AMF) as bioprotector agents against wilt induced by Verticillium spp. in pepper: a review - Goicoechea, N.; Garmendia, I.; Sánchez-Díaz, M.; Aguirreolea, J. (Spanish Journal of Agricultural Research, 2010)
Verticillium dahliae Kleb. is a vascular pathogen that alters water status and growth of pepper plants and causes drastic reductions in yield. Its control is difficult because it can survive in field soil for several years. The application of arbuscular mycorrhizal fungi (AMF) as bioprotector agents against V. dahliae is an alternative to the use of chemicals which, in addition, is more respectful with the environment. The establishment of the mutualistic association of plant roots and AMF involves a continuous cellular and molecular dialogue between both symbionts that includes the preactivation of plant defense responses that may enhance the resistance or tolerance of mycorrhizal plants to soil-borne pathogens. Some AMF can improve the resistance of Capsicum annuum L. against V. dahliae. This is especially relevant for pepper cultivars (i.e. cv. Piquillo) that exhibit high susceptibility to this pathogen. Compared with non-mycorrhizal plants, mycorrhizal pepper can exhibit more balanced antioxidant metabolism in leaves along the first month after pathogen inoculation, which may contribute to delay both the development of disease symptoms and the decrease of photosynthesis in Verticillium-inoculated plants with the subsequent benefit for yield. In stems, mycorrhizal pepper show earlier and higher deposition of lignin in xylem vessels than nonmycorrhizal plants, even in absence of the pathogen. Moreover, AMF can induce new isoforms of acidic chitinases and superoxide dismutase in roots. Mycorrhizal-specific induction of these enzymatic activities together with enhanced peroxidase and phenylalanine ammonia-lyase in roots may also be involved in the bioprotection of Verticillium-induced wilt in pepper by AMF